Regional characterization of functional connectivity in patients with sleep apnea hypopnea syndrome during sleep. (28th July 2021) - Zhang, Tingting; Pan, Yu; Lian, Jiakai; Pang, Feng; Wen, Jinfeng; Luo, Yuxi
Abstract: Objective . Sleep apnea hypopnea syndrome (SAHS) induces abnormalities in brain function. This study aims to find features that can characterize the impact of SAHS on the brain functional connectivity (FC) during sleep. Approach . Seventy-eight participants (39 SAHS patients and 39 age-matched healthy controls) were recruited and underwent a whole night of polysomnography. The improved weighted phase lag index algorithm was utilized to evaluate FC in δ, θ, α, β, and γ bands of six EEG channels. The regional FC features were further constructed to characterize the asymmetries of FC between the left and right hemispheres, the imbalances of FC between the inter- and intra-hemispheres, and those between the anterior and posterior cortex, respectively. Then, support vector machines and feature evaluation were used to verify the discriminative ability for the abnormal FC in SAHS patients of the above-mentioned features. Main results. The study observed abnormal FC changes in SAHS patients during sleep in multiple frequency bands. Moreover, regional FC features performed better in SAHS screening, and important features were mainly distributed in β and γ bands. Significance . Our research exhibited the abnormal regional FC in SAHS patients during sleep, which provided new insights and established indicators to investigate the changes of brain function in patients.